Trends in colorectal cancer incidence among younger adults—Disparities by age, sex, race, ethnicity, and subsite - Amanda B. Crosbie; Lisa M. Roche; Linda M. Johnson; Karen S. Pawlish; Lisa E. Paddock; Antoinette M. Stroup (Cancer Medicine)
Abstract Millennials (ages 18‐35) are now the largest living generation in the US, making it important to understand and characterize the rising trend of colorectal cancer incidence in this population, as well as other younger generations of Americans. Data from the New Jersey State Cancer Registry (n = 181 909) and Surveillance, Epidemiology, and End Results program (n = 448 714) were used to analyze invasive CRC incidence trends from 1979 to 2014. Age, sex, race, ethnicity, subsite, and stage differences between younger adults (20‐49) and screening age adults (≥50) in New Jersey (NJ) were examined using chi‐square; and, we compared secular trends in NJ to the United States (US). Whites, men, and the youngest adults (ages 20‐39) are experiencing greater APCs in rectal cancer incidence. Rates among younger black adults, overall, were consistently higher in both NJ and the US over time. When compared to older adults, younger adults with CRC in NJ were more likely to be: diagnosed at the late stage, diagnosed with rectal cancer, male, non‐white, and Hispanic. Invasive CRC incidence trends among younger adults were found to vary by age, sex, race, ethnicity, and subsite. Large, case‐level, studies are needed to understand the role of genetics, human papillomavirus (HPV), and cultural and behavioral factors in the rise of CRC among younger adults. Provider and public education about CRC risk factors will also be important for preventing and reversing the increasing CRC trend in younger adults.